Analisis Penerapan Akuntansi Zakat Dalam Laporan Keuangan Organisasi Pengelola Zakat Menurut Psak Nomor 109 Sebagai Tolak Ukur Kinerja Organisasi (Studi Kasus BAZNAS Kabupaten Banyumas) - Deri Pramana Putra; Anggita Isty Intansari (CV. ALIM'SPUBLISHING, 2023)
Zakat is a worship that has high social value, so that it can improve people's welfare. The higher the level of zakat acquisition, the better it is to improve people's welfare. The total acquisition of zakat in Indonesia, especially in Banyumas Regency is still not in accordance with the potential of existing zakat. BAZNAS Banyumas Regency plays an important role in increasing the acquisition of zakat according to the potential that exists in Banyumas Regency. Good zakat management is inseparable from accurate zakat accounting. The purpose of this study is to find out how the technique of applying zakat accounting and its conformity to PSAK 109 and the application of zakat accounting transparency at BAZNAS Banyumas Regency. This study used qualitative research methods. Data collection techniques used in this study were observation, interviews and documentation. The object of this study was carried out at BAZNAS, Banyumas Regency regarding the analysis of the application of zakat accounting. Based on the results of the study, it shows that the techniques applied in accounting for zakat at BAZNAS of Banyumas Regency are in accordance with PSAK 109. The exchange rate at BAZNAS of Banyumas Regency is prepared based on the concept of historical prices. Receipt of funds consists of zakat funds, infaq/alms, grants, APBD, and non-halal funds (banks and current account services). The application of transparency related to zakat accounting at BAZNAS in Banyumas Regency is still not optimal.